2010
DOI: 10.1002/cbdv.200800300
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids and Diterpenoids from Chloranthus anhuiensis

Abstract: A phytochemical investigation of the roots of Chloranthus anhuiensis afforded three new sesquiterpene lactones, chloraniolide A (1), (3R)-3-hydroxyatractylenolide III (2), and 8beta-hydroxy-1-oxoeudesma-3,7(11)-dien-12,8alpha-olide (3), and two new diterpenoids, (12R,13E)-15-(acetoxy)-12-hydroxylabda-8(20),13-dien-19-oic acid (4) and (12S,13E)-15-(acetoxy)-12-dihydroxylabda-8(20),13-dien-19-oic acid (5), as well as 17 known sesquiterpenoid and diterpenoid compounds. Their structures were established on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…More recently, several studies explored the use of Istanbulins as insect antifeedants and fungicidal, cytotoxic, phytotoxic, antioxidant, anti-inflammatory and antimicrobial agents, among other applications (see, for example, Reina et al, 2012;Fu et al, 2015). Although most of the reported compounds were obtained from the Smyrnium genus, there are some examples which were isolated from others, such as Sarcandra (Zen & Luo, 1983;Wang et al, 1988;Zhu et al, 2008), Chloranthus (Fu et al, 2015;Xu et al, 2010), Salvia (Aydog muş et al, 2006) and Senecio (Glauco et al, 1986;Ló pez-Rodríguez et al, 2009;Reina et al, 2001). Regarding the Senecio genus, the compounds obtained were Istanbulins A and B, and these were isolated from plants located in Chilean regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, several studies explored the use of Istanbulins as insect antifeedants and fungicidal, cytotoxic, phytotoxic, antioxidant, anti-inflammatory and antimicrobial agents, among other applications (see, for example, Reina et al, 2012;Fu et al, 2015). Although most of the reported compounds were obtained from the Smyrnium genus, there are some examples which were isolated from others, such as Sarcandra (Zen & Luo, 1983;Wang et al, 1988;Zhu et al, 2008), Chloranthus (Fu et al, 2015;Xu et al, 2010), Salvia (Aydog muş et al, 2006) and Senecio (Glauco et al, 1986;Ló pez-Rodríguez et al, 2009;Reina et al, 2001). Regarding the Senecio genus, the compounds obtained were Istanbulins A and B, and these were isolated from plants located in Chilean regions.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Senecio (Asteraceae) is widely distributed throughout the world, except for Antarctica and Amazonas, and includes more than 3000 species. It is well known that the Senecio species are used in folk medicine; their properties are attributed to their essential oils and secondary metabolites (Arancibia et al, 2010(Arancibia et al, , 2018El Hawary et al, 2008;Yang et al, 2011;Singab et al, 2013;Bohlmann et al, 1986;Romo de Vivar et al, 2007;Juarez et al, 1995;Xu et al, 2010;de Salmeron et al, 1983). Senecio filaginoides DC is one of the about 300 species which occurs in Argentina, growing from the Jujuy (north) to Santa Cruz provinces (south).…”
Section: Introductionmentioning
confidence: 99%
“…Chloranthus anhuiensis , belonging to genus Chloranthus , is distributed mainly in Anhui Province, P. R. China. The related research on this plant is rarely, and our previous article reported large quantity of sesquiterpene lactones and diterpenes, and some of them exhibited significant neuroprotective activity via activating the Akt signaling pathway . For the ongoing search for this plant, 15 compounds including three new compounds (7 S ,8 R )‐1‐(1‐ethoxy‐2‐hydroxypropyl)‐2‐methoxy‐3,4‐(methylenedioxy)benzene ( 1 ), (7 S ,8 S )‐1‐(1‐ethoxy‐2‐hydroxypropyl)‐2‐methoxy‐3,4‐(methylenedioxy)benzene ( 2 ), and (7 S ,8 R )‐1‐(1‐methoxy‐2‐hydroxypropyl)‐2‐methoxy‐3,4‐(methylenedioxy)benzene ( 3 ) were isolated and characterized from this plant ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…dysidiolide,60,86 manoalide,59,87 zerumin B,88 cacospongionolides,89 yangjinhualine A, 90 microperfuranone,91 antrocinnamomin D,92 chloraniolide,93 caribenol A94 και ένας ανταγωνιστής του υποδοχέα της ενδοθελίνης-Α (ανταγωνιστής Cl-1020 ή PD 156707, Σχήμα 3.2). σύνθεση αυτών των βιοδραστικών πυριδαζινών πραγματοποίηθηκε από την ερευνητική ομάδα του Lamberth, η οποία μάλιστα τον ίδιο χρόνο ανέπτυξε και μία νέα μεθοδολογία σύνθεσης γ-υδρόξυβουτενολιδίων, μέσω συμπύκνωσης τύπου Knoevenagel α-κετο εστέρων και αρυλο ακετονών (Σχήμα 3.5) 98.…”
unclassified
“…b) Δομή της βιταμίνης C, ενός πολύ γνωστού βουτενολιδίου.Πιο συγκεκριμένα, τα γ-υδροξυβουτενολιδικά δομικά μοτίβα παρουσιάζουν ξεχωριστό συνθετικό ενδιαφέρον, αφού συναντώνται σε μεγάλο ποσοστό των φυσικών προϊόντων και διακρίνονται σε αυτά που είναι υποκατεστημένα στη γ-θέση και σε μη υποκατεστημένα (υδρογόνο στη γ-θέση). Ενδεικτικά παραδείγματα φυσικών προϊόντων[86][87][88][89][90][91][92][93][94][95][96] που ενσωματώνουν τέτοιους γ-υδροξυβουτενολιδικούς δακτυλίους είναι τα 95 Σχήμα 3.2: Δομές φυσικών προϊόντων που φέρουν γ-υδρoξυβουτενολιδικούς δακτυλίους.3.2 Μεθοδολογίες σύνθεσης γ-υδροξυβουτενολιδίωνΗ αφθονία του δομικού μοτίβου των γ-υδροξυβουτενολιδίων στη φύση, καθώς και η σπουδαία βιολογική δραστικότητα που παρουσιάζουν τα φυσικά προϊόντα που ενσωματώνουν τέτοιους δακτυλίους, ώθησαν την επιστημονική κοινότητα στην αναζήτηση και ανάπτυξη πολλών μεθοδολογιών για τη σύνθεση αυτών των ενώσεων.Μία από αυτές τις μεθόδους, περιλαμβάνει την αλδολική συμπύκνωση ενός γ-κετο εστέρα με μια αλδεΰδη. Στη συνέχεια, το προϊόν της αντίδρασης υφίσταται αφυδάτωση σε όξινες συνθήκες, ισομερισμό του διπλού δεσμού και κυκλοποίηση προς σχηματισμό του γ-υδροξυβουτενολιδίου (Σχήμα 3.3).…”
unclassified